Analysis for Science Librarians of the 2015 Nobel Prize in Physics: Missing Neutrinos, Oscillations, and the New Science of the Ghostliest Particle. Issue 1 (2nd January 2016) - Bohémier, Kayleigh Ayn
ABSTRACT: The Royal Swedish Academy of Science announced that the Nobel Prize in Physics for 2015 would go to Arthur B. McDonald (Queen's University, Ontario, Canada) and Takaaki Kajita (University of Tokyo, Japan) for their pioneering work in detecting and constraining neutrino oscillations, a phenomenon in which one type of neutrino becomes another type of neutrino as it travels through space. This article describes the science behind the prize, provides an overview of scientific contributions that Kajita and McDonald have made to the field of neutrino astronomy, and analyzes citation and authorship patterns for each Nobel prizewinner.